The Effect of Capital Strengthening, Corporate Governance Implementation, and Risk Management on Financial Performance and its Implications for Business Sustainability at PT BPR Rama Ganda Bogor - Linda Sri Rezeki; Cecep Taofiqurrochman; Tatang S Herisman (Eduvest - Journal of Universal Studies, 2026)
This study examines the influence of capital strengthening, corporate governance implementation, and risk management on financial performance and its implications for the business sustainability of PT BPR Rama Ganda Bogor during 2017–2024. The study is motivated by the critical need to integrate these three elements to maintain the stability and competitiveness of rural banks (BPR) amid global economic challenges, the pandemic, and increasing regulatory pressures. Financial performance is measured using CAR (Capital Adequacy Ratio), LDR (Loan to Deposit Ratio), NPL (Non-Performing Loan), and ROA (Return on Assets), while business sustainability is evaluated based on the bank’s ability to develop products, maintain customer trust, and comply with sustainable finance principles. Descriptive analysis indicates an average CAR of 21.36%, LDR of 90.01%, NPL of 11.30%, and ROA of 3.25%, reflecting adequate capital stability and sufficient liquidity but room for improvement in asset quality. Findings reveal that capital strengthening, corporate governance, and risk management collectively have a significant impact on financial performance. Furthermore, strong financial performance positively influences business sustainability, including regulatory compliance, expansion of sustainable credit portfolios, and maintenance of stakeholder confidence. The study emphasizes that the synergy between capital, governance, and risk management must be internalized integrally into organizational culture and strategy, enabling BPR to manage risks effectively, maintain profitability, and ensure long-term business continuity. The results provide strategic recommendations for BPR and similar microfinance institutions to optimize capital, governance, and risk management as foundations for growth and sustainable operations in an uncertain economic environment.